Achieving the target crystal size distribution in the case of agglomeration and breakage for batch cooling crystallisation process - Zakirah, Mohd Zahari; Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (Italian Association of Chemical Engineering - AIDIC, 2017)
One of the main specification of crystallisation process is the crystal size distribution (CSD). In order to achieve the desired CSD, supersaturation or temperature control is applied to maintain the concentration or temperature at the required set-point trajectory which lies within the metastable zone. The set-point trajectory can be determined using the analytical CSD estimator where both the supersaturation/concentration set-point and batch time needed to achieve the desired target CSD can be estimated. The current analytical CSD estimator is applicable only for growth dominated phenomena and neglects the effects of agglomeration and breakage phenomena. Both phenomena occurs during crystallisation operation and may influences the CSD. Both agglomeration and breakage phenomena need to be considered during crystallisation operation in order to provide an accurate set-point trajectory and also to identify the effects of both phenomena on the performance of CSD. The objective of this work is to extend the analytical CSD estimator to cover the effects of agglomeration and breakage phenomena. Here the agglomeration and breakage phenomena are represented by kinetic power law equation and incorporated into the extended analytical CSD estimator. The application of this work is highlighted through a sucrose batch cooling crystallisation process case study where based on the identified target CSD, the extended analytical estimator is capable to generate the required setpoint trajectory. The proposed controller is successfully maintained the operation at the desired set-point and achieving the target CSD in the case of agglomeration and breakage.